Planeación financiera y su incidencia en los canales de créditos de los productores cacaoteros, del cantón Quinsaloma, año 2014 - Castro Trujillo, Lissette Adriana (2016)
This research project aims to perform a Financial Planning and its impact on the Credit Channel of cacao producers, the Quinsaloma Canton, 2014. For this purpose the following objectives: Diagnose the financial management mechanisms and short long term have been taken in cocoa crops in Quinsaloma Canton, analyze the impact of future channel more suitable for local producers credits, propose some alternative model for financial planning in cocoa crops Quinsaloma Canton. Within the methodology used are the location, types of research, methods and analytical and descriptive, sources of collection, research design, the instruments used and the processing of data which the sample was taken 82 between administrative staff and members, who were surveyed, which allowed them to assess the level of performance of the project partnership. Financial Planning conducted by the following conclusion: To conclude this final work could understand the importance of the distribution channels and their respective rates; however the data collection was not quite easy as it sounds, take hours of careful reading and understanding knowledge, would be helpful in this paper and could be used as a supporting annex; in regard to the importance of physical distribution I can say that without it we would not know where we are because there is something very useful and important it is that states that makes the difference between success and failure, this l This study will as a guide to enable the members of the organization to identify the profitability and viability of the business, this being a useful tool to evaluate the project.